PP-035 The outcome of microbiological monitoring in cytotoxic drug preparation. (14th February 2016) - Moreira, S; Jorge, A; Oliveira, C; Glória, F; Ferreira, J; Branco, J; Carvalho, M; Cândido, S; Ferrer, C
Abstract : Background: Microbiological contamination risk can be minimised using a vertical laminar flow cabinet placed in a clean room. Cytotoxic drugs must be prepared according to the work instructions in order to guarantee that all of the quality, hygiene and disinfection standards are complied with. 1, 2 Purpose: To assess the outcome of microbiological control (MC) in cytotoxic (CTX) preparations. Material and methods: The MC is executed by pharmacists according to hospital procedures for the working environment (WE), sterile preparation (SP) and glove fingertips (GF) at the end of each working session, on the background environment (BE) and WE surface (SWE) weekly, and on the BE surface (SBE) monthly. Blood agar plates are used for these controls, with the exception of SP (calcium folinate) that are made in brain-heart infusion. A retrospective analysis was performed from April 2014 to August 2015. Results: 492 samples were tested. The contaminations identified in WE, SWE, BE, SBE, GF and SP controls were 1%, 3%, 18%, 6%, 14% and 2%, respectively. Results obtained for BE and SBE were within the limits for zone B (<5 CFU), contrary to those found in WE and SWE (>1 CFU) in which staphylococcus and micrococcus that are common on human skin predominated. Because of the high number of positive controls in GF, additional tests were made in CTX and sterile gloves and fingers. Sphingomonas paucimobilis and Staphylococcus epidermidis detected in GF matched the bacteria found on the CTX gloves, and so it was necessary to change CTX gloves as they were not appropriate. Staphylococcus warneri was detected on the fingers, which reinforced the importance of good practices concerning washing hands. After 3 consecutive days of SP positive results, it was decided that the pathology laboratory should use sterile gloves when handling these samples. After 6 months of SP negative controls, there was one positive so it was decided to store a sample of SP in order to allow a counter-analysis. After this, all SP positive controls had negative counter-analysis. Conclusion: Positive MC should trigger corrective/preventive measures. 1 Identification of each bacteria proved to be crucial in determining the possible cause of infection, thus allowing its elimination. The MC is a good indicator for early detection of problems and definition of corrective actions. References and/or Acknowledgements: Cytotoxic Preparation Manual. Portuguese Pharmaceutical Society, 2013. Hospital Pharmacy Manual. INFARMED, 2005. No conflict of interest.